Analysis of The Welfare Level of Palm Farmers at Sungai Sayang Village - jumliadi, Jumliadi; Musthofa, M. Arif; Nurjali, Nurjali (Zabags International Journal of Economy, 2024)
The aim of the research is to analyze and determine the influence of the level of welfare of oil palm farmers in Sungai Sayang Village, Sadu District, and to find out what obstacles are often faced in improving the welfare of oil palm farmers in Sungai Sayang Village, Sadu District. In this research the author used a qualitative approach with descriptive analysis methods. The level of welfare of oil palm farmers also depends on the farmer's income, especially the income obtained from oil palm plantations, so the higher the farmer's income from oil palm, the level of welfare of oil palm farmers will also increase. And also, the obstacles faced by oil palm farmers in Sungai Sayang Village are the unstable selling price of palm oil FFB, and also inadequate road conditions making it difficult to transport the community's palm oil FFB products. The results of this research are that the level of welfare of oil palm farmers also depends on the farmer's income, especially the income obtained from oil palm plantations, so the higher the farmer's income from oil palm, the level of welfare of oil palm farmers will also increase. The obstacles faced by oil palm farmers in Sungai Sayang Village are the unstable selling price of palm oil FFB, and also inadequate road conditions making it difficult to transport the community's palm oil FFB products.